Beyonderground : a 2-day Creative ego Nightmare/Festival : 13. - Duval, Stephanie ([S.l.] : Stephanie Duval, 2013)
Kohno, Ai ; Beaunanza ; Brutal Knitting ; Bureau Bruneau ; BVD ; DJ Food ; Ephameron ; van Halem, Hansje ; Newman, Hattie ; HORT ; Hugo & Marie ; I Like Birds ; Griffin, James ; Rewell, Janine ; Julien, Jules ; Kokoro & Moi ; Luyckx, Kristof ; Letman ; Letterproeftuin ; Pyper, Martin ; Hugo, Mario ; McBess ; Hos, Merijn ; Mijn Schatje ; Ninjato ; OS OVNI ; Abad, Pablo ; Kraft, Patrick ; Jenkins, Paul ; Buczkowski, Piotr ; Playtype ; Pointdexter ; Sauerkids ; Serial Cut ; Jackson, Trevor ; Gattoni, Ugo ; Wasted Rita ; YCN ; Hvass&Hannibal ; Mads ; Pot, Bertjan ; Forbach, Mathias ; Eggertson, Siggi ; Brusatto, Geoffrey ; d[x]i + visualcache ; FriendsWithYou ; adidas Originals ; Eike König + Elsa Mora ; Emilie Gervais + Os Ovni ; Q-TA + Sienna Freeman
boek